M-Learning Module for Self-Directed Language Learning; a Study of Students’ Needs Analysis - Nurizah Md. Ngadiran; Nor Aziah Alias; Nadia Anuar (Development in Language Studies, 2021)
Self-directed learning has attained significant scholarly recognition as it promotes students to take charge of their learning pace. Thus, the central thesis of this paper is to identify students’ needs for a mobile learning module to encourage self-directed learning among students. This study examines the students’ needs based on four facets which are hardware, operational platforms, concepts, and learning strategies for the development of the mobile learning module, TutorMe. The needs analysis data were collected by administering questionnaires to 74 students. The results revealed that respondents’ preferred hardware was smartphones while the learning management system (LMS) was indicated as the preferred operational platform for TutorMe. The results also demonstrated that the respondents’ preferred learning strategy for TutorMe was self-learning and for TutorMe to be used during independent study hours (ISH). The development of TutorMe has provided an important opportunity to advance our understanding of students’ needs to encourage students’ participation in self-directed learning.